An antioxidant- and hydroxymethylfurfural-based index for health impact grading of honey - Yap, Shu Khang; Chin, Nyuk Ling; Niranjan, Keshavan; Abdul Karim Shah, Nor Nadiah; Than, Leslie Thian Lung (Springer, 2024)
Honey quality is conventionally controlled by checking its compliance with the regulatory standards mainly through physical properties. A new index of honey quality known as the Honey Health Impact Metric (HHIM) which considers two main parameters related to health was developed for use as a more market-relatable criteria in the honey industry. The HHIM incorporates the balancing of the positive health-beneficial 2,2-diphenyl-1-picrylhydrazyl (DPPH) radical scavenging activity with the negative health-detrimental hydroxymethylfurfural (HMF) concentration present in honey. It is defined as the average score between fractional DPPH and the normalised HMF. The HHIM was tested using 30 randomly selected honey samples from different origins which were then graded by the different categories of quality. As both parameters are also affected by honey storage period, the HHIM was also used to monitor changes in two specific honey samples, the Kelulut Itama and Tualang Dorsata. With quality of honey deteriorating over storage time following a zero-order kinetic model, the indications by HHIM gave a storage recommendations of 10 to 12 months for both these honey samples. This idea of HHIM as an alternative honey quality indicator to gauge health potential of honey will support the genuine and real products in the honey industry.